Cochlear implantation in children with prelingual deafness: literature review (Research, Society and Development, 2021)
Cochlear implant (CI) represents one of the most important advances in the treatment of children with prelingual hearing loss. In childhood, hearing alterations cause delay in speech and language development. In this sense, the earlier the diagnosis, the greater the tendency to minimize these delays. The aim of this study was to assess the speech development of children with prelingual deafness after cochlear implantation. The study represents an integrative literature review where data was collected in October 2021 through the search for articles in the Lilacs, SciELO, MEDLINE (Via BVS) databases, using the descriptors: “hearing”, “cochlear implant”, “language” and “pre-lingual” and which were combined using the Boolean operator “AND”. Fully available articles, published between 2012 and 2021 in Portuguese, English and Spanish, were included. Articles published outside the chosen period that did not address the theme of work, dissertations and theses, and duplicates were excluded. Eighty-two articles were found, where a screening was performed with the reading of titles and abstracts, 58 of which were excluded for not addressing the topic, resulting in 24 articles that totaling 6 articles included in the review. Publications reported the age factor as extremely relevant in the early speech enabling process, as the earlier the implementation, the better the speech development. The CI is effectively satisfactory for speech development.